Determination of the tendency of imprudent behavior and malpractice in nursing students of a state university - Cevik Durmaz, Yadigar; Kaplan Serin, Emine; Dogan, Runida; Isik, Kevser (Annals of Medical Research, 2021)
Aim: This study was conducted to determine the tendency of imprudent behavior and malpractice in nursing students of a state university. Materials and Methods: The sample of this descriptive cross-sectional study consisted of 103 students. Results: The vast majority of the students indicated factors such as small number of nurses working, high workload, fatigue, stress and loading nurses with off-duty jobs as causes of medical malpractice. Conclusion: The majority of medical malpractices occur due to preventable imprudent behavior. Although the tendency of nurses to perform medical malpractice appears to be low, providing trainings on reducing medical malpractices may contribute to raising awareness on patient safety.